Analysis of Online Sales Applications in Rendang Mala Business at Payakumbuh City - Andi Putra; Khairul Annisa; Arif Rizki Marsa (International journal of technology and education research, 2023)
Rendang Mala is one of the rendang businesses in the city of Payakumbuh. So far, the business of selling Mala rendang is still done manually, that is, buyers go directly to the store to get the product. In today's all-online digital era, internet-based innovation is needed that can support the business world to facilitate buying and selling transactions, streamlining time and distance so that buyers don't have to come to the store to get products. The web-based online sales application is designed to make it easier for consumers to get Mala rendang products. Web-based online sales application for Mala's rendang business developed with use Language programming databases, PHP, and MySql. For know satisfaction user to application This done study with use model PIECES analysis. Based on the results of the study using PIECES analysis, an average score of 4.4 . Which showing that application online sales give results